Knowledge, attitude and practice towards COVID-19 among workers of a tertiary hospital in Bayelsa State, Nigeria - Egbi, Oghenekaro Godwin (Pan Afr Med J, 2020)
INTRODUCTION: coronavirus disease (COVID-19) has since assumed pandemic dimensions with over 14million persons affected in 213 countries and territories worldwide as at mid-July 2020. The level of awareness and knowledge of the disease as well as the related attitude and practice amongst hospital workers could determine its extent of control. The aim of this study was to determine the knowledge, attitude and practices amongst hospital staff regarding COVID-19. METHODS: this cross-sectional study was conducted among staff of the Niger Delta University Teaching Hospital, Bayelsa State, Nigeria. A self-administered semi-structured questionnaire was adapted in assessing their knowledge, attitude and practice towards COVID-19. RESULTS: one hundred and twenty four respondents completed the study with a mean age of 30.9 ± 6.5 years. Up to 90% of them demonstrated good knowledge of COVID-19 with regard to preventive and control measures. Approximately 90% of them practiced good hand hygiene though a lesser proportion wore face masks (51.6%) and practiced crowd avoidance (58.1%). Medical doctors had a marginally higher practice score compared with “others” (p = 0,047). Up to 98(79.0%) of respondents were scared of self-infection and 99(79.8%) were not motivated to work due to inadequate facilities, equipment and resources in 50% of cases. Knowledge of COVID-19 was positively correlated with the practices of the participants (p = 0.023). CONCLUSION: the hospital staff lacked adequate motivation towards management of COVID-19 and were constrained for the fear of self- infection, inadequate equipment, resources and equipment despite possessing a good knowledge of the disease. There is need for concerted efforts by stakeholders in the health care industry to ensure hospital workers are adequately motivated and provided with the needed risk protection devices and resources during this pandemic.